(untitled) - Stead, Alfred (London, 1906)
In this book it is by no means my intention to compare the national efficiency of Japan with that of other nation; my object is simply to give examples from various sides of national life in that country which demonstrate the advantagees effects to be derived from a universal and practical patriotism...